THE ALLOMORPHY IN ENGLISH WORDS: MORPHOLOGY AND PHONOLOGY INTERRELATED APPROACH - Tarigan, Karana Jaya; Sembiring, Milisi (Universitas Islam Sumatera Utara (UISU), 2023)
The article aims to analyze which allomorphs occur more accurately in English and what factors determine them. The problems that the researchers examine enable English learners and readers to pronounce English words, in this case, English morphemes. The theory employed by the researchers is morphophonemics, dealing with how morphemes alter their appearance or pronunciation in response to the sounds that surround them in a given piece of content. The approach or method that the researchers use in this article is descriptive qualitative method based on the data. The findings that the researchers come across are as follows: (a) the definitive article, (b) the definitive article, (c) Derivation, (d) Irregular verbs, (e) Past tense marker (-ed), (f) Present tense morpheme, (g) Plural noun markers, (h) Possessive markers. It can be seen that the shape or pronunciation of an English word depends on the linguistic environment in which it occurs, and it is obvious that morphophonemic change involves not only replacing but also changing the phonological shape of a morpheme. Based on the data, the researchers find that there are two basic types of allomorph, such as morphophonemic changes and suppletion. The researchers also attend to the theory of Pike, stating that sounds tend to be influenced by their environments.